2020
DOI: 10.1021/acs.est.9b07657
|View full text |Cite
|
Sign up to set email alerts
|

Trophic-Level Interactive Effects of Phosphorus Availability on the Toxicities of Cadmium, Arsenic, and Their Binary Mixture in Media-Exposed Scenedesmus acutus and Media and Dietary-Exposed Daphnia pulex

Abstract: Various anthropogenic activities simultaneously alter essential mineral nutrients and contaminant content in the environment. Depending on essential nutrient conditions, the uptake and effects of contaminants in exposed organisms may be altered. The addressing of ecological risk assessment (ERA) of contaminant mixtures has proven difficult. Furthermore, most assessments involving single contaminant exposures do not consider the interaction of essential nutrients on toxicological end points. Hypotheses for toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…For the design of mixture rays, as mentioned above, many scholars have been inclined to design in a single way. In this study, we used EquRay to design three binary mixture systems. The results show that the 15 mixture rays of the three systems show different toxicological interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the design of mixture rays, as mentioned above, many scholars have been inclined to design in a single way. In this study, we used EquRay to design three binary mixture systems. The results show that the 15 mixture rays of the three systems show different toxicological interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The equivalent-effect concentration ratio (EECR), specified proportion, and fixed proportion are commonly used by most of the scholars when designing mixtures. For example, Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Daphnia reared in LP can also increase the somatic concentrations of trace metals such as selenium and zinc (Browning et al, 2017;Guimarães et al, 2023;Wang et al, 2022), both of which have been shown to reduce As toxicity by increasing As methylation efficiencies, decreasing DNA damage and increasing metallothionein levels, respectively (Cooper et al, 2013;Zhao et al, 2019;Zwolak, 2020). Previous studies on the As-P interactions in Daphnia showed mixed results, with both negative (Miao et al, 2012) and positive interaction effects (Awoyemi et al, 2020;see Zhang et al, 2022). Another factor to consider when comparing As-P effects is the source of the As supply.…”
Section: Discussionmentioning
confidence: 99%
“…Daphnia pulex was acquired from Carolina Biological Supply Company (Burlington, NC, USA) and maintained as previously described [21]. Briefly, organisms were maintained in COMBO medium in a controlled Precision Low Temp BOD Refrigerated Incubator (VWR, Radnor, PN, USA).…”
Section: General Culture Methodsmentioning
confidence: 99%